Genetic and Molecular Testing in Thrombosis and Hemostasis: Informing Surveillance, Treatment, and Prognosis - Crispin, Philip; Koo, Ray Mun (Seminars in Thrombosis and Hemostasis, 2019)
The understanding of molecular mechanisms brought about by the rapid expansion of gene sequencing has helped to characterize molecular interactions underpinning normal hemostasis and identify inherited and acquired risks for thrombosis and hemorrhage. The widespread availability of molecular testing may serve to replace some currently available investigations with more precise diagnostic tools and add to phenotypic tests. Molecular studies will increasingly enable prenatal diagnosis, confirm difficult diagnostic challenges, early intervention, and assist in prognostication. This approach facilitates specific individualization of treatment options, with personally targeted therapy expected to increase. There remain many challenges, however, in the clinic. Prior to any test there should be consideration of how the results may influence treatment, and also how they may affect the patient within their familial and social environments. Massive parallel sequencing has the capacity to produce results that create uncertainty that needs to be considered prior to testing. In this context, the potential benefits of adding phenotypic and genotypic personal data to large databases should be discussed with patients. There is a paradox in that personalized medicine is dependent on large datasets to interpret the significance of genetic variation. This review will provide an outline of specific current and emerging roles for molecular testing for the personalization of care in the practice of thrombosis and hemostasis and highlight principles that can be implemented as new opportunities inevitably arise with the rapid expansion of knowledge from genomics.
Keywords: human genetics; genetic counseling; thrombophilia; inherited blood coagulation disorders